Unilateral Dual‐Plane Puncture Percutaneous Vertebroplasty Reduces Re‐Collapse in Osteoporotic Vertebral Compression Fractures by Advancing Cement Delivery - Huo‐Liang Zheng; Chang‐hai Liu; Lei‐Sheng Jiang; Xin‐Feng Zheng; Sheng‐Dan Jiang (Orthopaedic Surgery)
ABSTRACT Purpose Evaluate the efficacy of a novel unilateral dual‐plane puncture technique in improving bone cement distribution and reducing vertebral re‐collapse following percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fractures (OVCFs). By introducing the novel unilateral dual‐plane puncture technique, this study aims to improve cement distribution, reduce the incidence of re‐collapse, and enhance long‐term clinical outcomes for patients suffering from OVCFs. Methods This is a randomized trial conducted from April 2021 to December 2022, enrolling 145 patients diagnosed with OVCFs. Patients were allocated into either traditional or unilateral dual‐plane puncture groups. Bone cement distribution, vertebral height, and segmental kyphotic angle were measured through postoperative x‐ray, while clinical outcomes were evaluated using the Visual Analog Scale (VAS) and the Oswestry Disability Index (ODI). Statistical analysis was performed using the Mann–Whitney U test and independent samples t test for continuous variables, and chi‐square or Fisher's exact test for categorical variables. Results The unilateral dual‐plane puncture technique notably augmented bone cement contact with both superior and inferior endplates compared to conventional methods, achieving rates of 64.86% versus 40.85% (p < 0.001). This contributed to a significant reduction in the incidence of vertebral re‐collapse within the first year post‐operation: 18.92% in the unilateral dual‐plane group as opposed to 42.25% in the traditional group (p < 0.001). Furthermore, the unilateral dual‐plane group exhibited markedly superior long‐term efficacy, evidenced by mean VAS and ODI scores of 1.26 and 28.58, respectively, in comparison to 2.03 and 32.45 in the traditional group. Conclusions The unilateral dual‐plane puncture technique advances bone cement distribution within the vertebra, thereby reducing the risk of vertebral re‐collapse following PVP surgery and improving long‐term clinical outcomes for patients with OVCFs.